Petrographical and Geochemical Characteristics of Felsic Volcanic Rocks in the Upper Part of The Khorat Plateau, Thailand - Singtuen, Vimoltip; Seela, Thatchapon (Indonesian Journal on Geoscience, 2025)
The felsic volcanic rocks distributed in the western part of Nong Khai and Udon Thani Provinces are part of The Loei-Phetchabun Volcanic Belt. This study aims to investigate the petrography and geochemical characteristics of felsic volcanic rocks to classify specific names of rocks and explain their occurrences. The textures and compositions by petrographic analysis classify the studied rocks into four types: (1) rhyolite porphyry, (2) crystal tuff, (3) eutaxitic rhyolite porphyry, and (4) hornblende-biotite diorite. In addition, the total alkaline versus silica (Na2O+K2O/SiO2) ratios classify these rocks into rhyolite, dacite, and basaltic andesite/diorite intrusion. Moreover, the major oxides and trace elements indicate that these volcanic rocks were generated from tholeiitic, transitional, and calc-alkalic magma series that formed along volcanic arcs. Therefore, the subduction of at least two tectonic terranes in the area may lead to the formation of the volcanic arc (felsic volcanic rocks and hornblende-biotite diorite).